Design and fabrication of a rapid detection biosensor for Candida albicans diagnosis in a microfluidic platform - Shekoufeh Moradkhah; Mohaddeseh Larypoor; Abdollah Allahverdi (Talanta Open)
Candida species are opportunistic fungi that can lead to a wide range of infections in humans, ranging from superficial to systemic. The diagnosis and treatment of Candida infections present significant challenges due to the diversity and resistance of these species, as well as the lack of rapid and sensitive detection methods. Microfluidics presents an opportunity to develop quick and highly sensitive diagnostic devices, enabling disease detection with minimal sample volumes. This study aimed to design and fabricate a microfluidic chip for the rapid and sensitive detection of Candida albicans in clinical samples. The dimensions of the chip were approximately 3.5 × 3.5 cm. The master chip was fabricated using soft lithography, and replicated in polydimethylsiloxane (PDMS), a biocompatible and transparent elastomer, which was treated with plasma to activate its surface. The study found that 150 samples (75 %) tested positive for Candida species, with Candida albicans being the most prevalent species at 58 %, followed by other non-albicans Candida species. Additionally, the study revealed that Candida infections were more common among women, young adults, the elderly, and patients with gastrointestinal diseases. The microfluidic chip demonstrated the ability to detect Candida albicans in clinical samples with a low detection limit of 10 CFU/mL. The study concluded that the microfluidic chip is a promising tool for diagnosing Candida infections in point-of-care settings and emphasized that Candida infections represent a common and diverse issue among patients.